2017
DOI: 10.1089/cyber.2016.0362
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Attitudes of Classes of College Students Who Use Pornography

Abstract: Pornography is widely accepted and used as an appropriate sexual practice. Previous literature has suggested that pornography users may be best viewed through a heterogenetic lens that indicates specific classes of pornography users. Furthering this previous research, a latent profile analysis was conducted using a sample of 635 college students (mean age men 20.22 (standard deviation [SD] = 3.10); women 19.16 [SD = 2.12]) over two time points to not only identify unique classifications of pornography users, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
6
15
1
Order By: Relevance
“…With regard to cognitive biases and the attitude toward IP, it has been shown that unregulated IP use was associated with more positive implicit associations (Snagowski, Wegmann, Pekal, Laier, & Brand, 2015) and both approach (indicating a positive attitude) and avoidance tendencies (indicating a negative attitude) toward IP images . Furthermore, Brown, Conner, and Vennum (2017) could show that the acceptance of pornography and a general sexual permissiveness were associated with higher IP use. In addition, a more positive attitude toward IP has been associated with frequent IP use (Svedin, Akerman, & Priebe, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…With regard to cognitive biases and the attitude toward IP, it has been shown that unregulated IP use was associated with more positive implicit associations (Snagowski, Wegmann, Pekal, Laier, & Brand, 2015) and both approach (indicating a positive attitude) and avoidance tendencies (indicating a negative attitude) toward IP images . Furthermore, Brown, Conner, and Vennum (2017) could show that the acceptance of pornography and a general sexual permissiveness were associated with higher IP use. In addition, a more positive attitude toward IP has been associated with frequent IP use (Svedin, Akerman, & Priebe, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…This, in turn, creates a need to understand how these individuals may perceive pornography. For this reason, some studies have addressed this issue by investigating groups of college students but sample size was often not high or limited to only one gender [41,42,43,44,45,46]. This is, therefore, of interest to conduct further studies that would survey large groups and assess to which extent individual characteristics may affect differentiate the patterns of pornography use.…”
Section: Introductionmentioning
confidence: 99%
“…Third, three-wave cross-lagged longitudinal studies could be conducted, to definitively establish the time order of associations between pornography viewing, sexual attitudes, and sexual behavior. Science is a cumulative endeavor, and it is true that many longitudinal studies have now found that earlier pornography consumption is prospectively correlated with either later sexual attitudes or behavior (e.g., C. C. Brown, Conner, & Vennum, 2017;J. D. Brown & L'Engle, 2009;D'Abreu & Krahe, 2014van Oosten, Peter, & Vandenbosch, 2017Ward, Vandenbosch, & Eggermont, 2015;Wright, 2012).…”
Section: Discussionmentioning
confidence: 99%